(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The cultivated plants pests in Casamance area (Senegal) and their natural enemies are mentionned. Inventories made between 1980 and 1984 concern more than 35 cultivated plants. Almost complete lists are presented for rice, « diakhatou » and cassava. Dealing with other productions, further investigations are necessary. These original data for Casamance area constitute the basic step of an integrated pest contrai management.